Kết nối vận tải hàng hải trong vai trò giảm thiểu tác động tiêu cực của khoảng cách địa lý đối với xuất khẩu của Việt Nam - Huỳnh Thị Diệu , Linh; Hoàng Thanh, Hiền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study was conducted to analyze the effects of bilateral maritime transport connectivity on Vietnam's export value to 40 coastal countries that are its major export partners over a ten-year period from 2011 to 2020. Various tests are applied to ensure that the two-step system Generalized Method of Moments estimation method used in the study is consistent, unbiased, and appropriate. The estimated results of most of the variables are statistically significant and are consistent with the hypotheses of the gravity model. The experimental results not only confirm the importance of maritime transport connectivity for Vietnam's exports but also conclude that an effective bilateral sea transport connection will help reduce the negative impact of geographical distance.
Keywords: Marine transport; Bilateral transport connection; GMM estimation; Exports; Vietnam